ACCURACY OF TRANSVAGINAL ULTRASOUND IN THE DIAGNOSIS OF ENDOMETRIAL POLYPS: A SYSTEMATIC REVIEW (The Research of Medical Science Review, 2025)
Background: Endometrial polyps are focal intrauterine endometrial neoplasm that may be single or multiple. Their size varies from few millimeters to several centimeters, and their morphology may be sessile with large or small implantation base or pedunculated. The aim of this study is to access the diagnostic accuracy of transvaginal ultrasound in the diagnosis of endometrial polyps in symptomatic as well as asymptomatic patients. Methods: This systematic review follows PRISMA guidelines. A comprehensive literature search was done including PubMed, Scopus and Google Scholar.Results: A total of 2040 articles were identified through database searching. After removing 140 duplicate records, 1900 articles remained for screening. During the title and abstract screening phase, 1750 articles were excluded due to irrelevance or not meeting the study criteria. This left 150 full-text articles for detailed eligibility assessment. Among these, 150 articles were further excluded due to reasons such as insufficient data, lack of comparative analysis, or methodological limitations. Finally, 10 studies were selected for inclusion in the systematic review and analysis.Conclusion: Transvaginal ultrasound proves to be a valuable and widely used tool for assessing endometrial abnormalities, its diagnostic limitations should be acknowledged. In cases where uncertainty remains, adjunctive testing should be considered to enhance accuracy and optimize patient management.